2021
DOI: 10.1016/j.redox.2021.102049
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy coordinates the mitochondrial unfolded protein response to attenuate inflammation-mediated myocardial injury

Abstract: Mitochondrial dysfunction is a fundamental challenge in septic cardiomyopathy. Mitophagy and the mitochondrial unfolded protein response (UPR mt ) are the predominant stress-responsive and protective mechanisms involved in repairing damaged mitochondria. Although mitochondrial homeostasis requires the coordinated actions of mitophagy and UPR mt , their molecular basis and interactive actions are poorly understood in sepsis-induced myocardial injury. Our investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(128 citation statements)
references
References 69 publications
3
125
0
Order By: Relevance
“…Two defensive mechanisms, mitophagy and the mitochondrial unfolded protein response, counteract mitochondrial deterioration. Urolithin A, a mitophagy inducer, diminishes systemic inflammation mediated cardiac depression, improving mitochondrial function [ 22 ]. In mice, deletion of the regulatory FUN14 domain-containing protein 1 (FUNDC1) inhibits calcium influx from the cytoplasm through the inositol 1,4,5-trisphosphate receptor type 2 (IP 3 R 2 ) and maintains mitochondrial integrity.…”
Section: Systemic Inflammatory Cytokines Influence Intracellular Calcium Homeostasis and Myocardial Contractilitymentioning
confidence: 99%
“…Two defensive mechanisms, mitophagy and the mitochondrial unfolded protein response, counteract mitochondrial deterioration. Urolithin A, a mitophagy inducer, diminishes systemic inflammation mediated cardiac depression, improving mitochondrial function [ 22 ]. In mice, deletion of the regulatory FUN14 domain-containing protein 1 (FUNDC1) inhibits calcium influx from the cytoplasm through the inositol 1,4,5-trisphosphate receptor type 2 (IP 3 R 2 ) and maintains mitochondrial integrity.…”
Section: Systemic Inflammatory Cytokines Influence Intracellular Calcium Homeostasis and Myocardial Contractilitymentioning
confidence: 99%
“…The heart is rich in mitochondria, which are involved in both energy provision and intracellular calcium regulation; consequently, the degree of mitochondrial dysfunction is tightly linked to SICD and the prognosis of this condition ( Lin et al, 2020a ; Shi et al, 2021a ; Wang et al, 2021a ). The activities of complexes I and II of the mitochondrial respiratory chain were diminished in the hearts from animals with sepsis ( Piel et al, 2007 ; Neviere et al, 2016 ), and this might be due to the detrimental effects of sepsis mediators such as NO, TNF-α, IL-1β, etc.…”
Section: Mechanisms Of Immune Regulation and Metabolism In Sepsis-induced Cardiovascular Dysfunctionmentioning
confidence: 99%
“…In septic rats, UPRmt is known to be downregulated under sepsis attacks ( Shen et al, 2021 ). Enhancement of endogenous UPRmt through oligomycin administration reduced sepsis-mediated mitochondrial injury and myocardial dysfunction through mitophagy ( Wang et al, 2021a ).…”
Section: N6-methyladenosine Facilitates Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Wang et al 's work showed that activation of FUNDC1-mediated mitophagy by UA, a mitophagy inducer, attenuated SICM in LPS-treated mice model (Wang et al, 2021). They found that the elevation of the levels of cardiac injury markers by LPS treatment is inhibited by UA administration in control mice but not in cardiomyocyte-specific FUNDC1 knockout mice (Wang et al, 2021).…”
Section: Fundc1 and Sepsis-induced Cardiomyopathymentioning
confidence: 99%
“…Wang et al 's work showed that activation of FUNDC1-mediated mitophagy by UA, a mitophagy inducer, attenuated SICM in LPS-treated mice model (Wang et al, 2021). They found that the elevation of the levels of cardiac injury markers by LPS treatment is inhibited by UA administration in control mice but not in cardiomyocyte-specific FUNDC1 knockout mice (Wang et al, 2021). The expression of mtUPR-related genes is significantly upregulated when FUNDC1 is deficient in LPS-treated heart, indicating that mtUPR is activated when mitophagy is blocked in response to LPS treatment (Wang et al, 2021).…”
Section: Fundc1 and Sepsis-induced Cardiomyopathymentioning
confidence: 99%